Increasing electronic nose recognition ability by laser irradiation - Massacane, Alejandra (2009)
We present a method to increase the capability of an electronic nose to discriminate between a priori similar odours. We analyze the case of olive oil because it is well known that the characteristics of its aroma impair in many cases the discrimination between different kinds of olive oils especially when they are from similar geographic regions. In the present work we study how to improve the electronic nose performance for the above mentioned discrimination by the use of two IR laser wavelengths for vaporization.